2022
DOI: 10.3390/biomedicines10081891
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Matrix Metalloproteinase Single-Nucleotide Polymorphisms in the Clinicopathological Properties of Breast Cancer

Abstract: (1) Background. Breast cancer is the leading cancer type among women. Despite convenient diagnostics at early stages, there is a need for continuous monitoring to predict more aggressive or recurring breast cancer forms. The evidence suggests that the detection of genetic biomarkers could help in improving disease management and reduce mortality. Matrix metalloproteinases (MMPs) are a large family of enzymes that perform physiologically relevant functions and have the potential properties to be biomarkers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Нарушение метаболизма коллагена в соединительной ткани может быть связано с полиморфизмом генов, регулирующих его синтез и формирование ВКМ [7]. Показано, что однонуклеотидные полиморфизмы (SNP) в промоторных областях генов MMP2 и MMP9 приводят к изменению уровня их экспрессии и, таким образом, могут быть связаны с предрасположенностью к различным заболеваниям.…”
Section: конфликт интересовunclassified
“…Нарушение метаболизма коллагена в соединительной ткани может быть связано с полиморфизмом генов, регулирующих его синтез и формирование ВКМ [7]. Показано, что однонуклеотидные полиморфизмы (SNP) в промоторных областях генов MMP2 и MMP9 приводят к изменению уровня их экспрессии и, таким образом, могут быть связаны с предрасположенностью к различным заболеваниям.…”
Section: конфликт интересовunclassified
“…In the case of gastric cancer, the meta-analysis showed that carriers of the TT genotype were at 1.666 times higher risk of that cancer when compared to carriers of the CC genotype ( Peng et al, 2017 ). The most recent publications also report the relationship between the MMP-9-1562C/T polymorphism and the risk of pre-eclampsia or breast cancer and its aggressiveness ( Gannoun et al, 2021 ; Bartnykaitė et al, 2022 ; Huang et al, 2022 ; Yan et al, 2022 ). It shows that the MMP-9-1562C/T polymorphism has a functional effect not only on brain cells but also on other cell types.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced-serum MMP8 level in CRC patients was significantly related to advanced-stage CRC, distant metastasis, lack of MMR, and poor survival [ 12 ]. Relevant studies have concluded that the polymorphisms of MMP8 are associated with the risk of a variety of cancers, including breast cancer [ 13 ], thyroid cancer [ 14 ], and laryngeal squamous cell carcinoma [ 15 ]. Previously, the association between MMP8 rs11225395 and CRC susceptibility has been reported [ 16 ].…”
Section: Introductionmentioning
confidence: 99%